The Harmonious Dialectics Between Hindu-Muslim in Bali (A Study in Jembrana Regency) - Saihu, Saihu; Şahin, Cemal (RELIGIA, 2020)
This paper discusses the harmonious dialectics process between Hindus and Muslims through‘urf or local wisdom which is believed to have philosophical, sociological, and psychological values with plural-multicultural nuances for the community of Jembrana, Province of Bali. This paper focuses on searching the effectiveness of some‘urf or local wisdom that functions as a means to interact between two religious communities that lead to peaceful practices on Hindu-Muslim communities in Jembrana-Bali. The data sources are field observations and unstructured interviews from March-July 2019. This study is field research using a method of a case study. The results found that the dialectics process with a multicultural nuance between Hindus and Muslims in Jembrana is through the‘urf or local wisdom, namely male, ngejot, rebana, and mekepung traditions. Further, from these four traditions, there is a process of active involvement, constructive understanding, and efforts to find joint commitments from various commitments, so that a sense of brotherhood and understanding of the diversity between the two religious communities becomes extremely close. This dialectic can also shape the character of Hindu and Muslim communities in Jembrana to be humanist, tolerant, and inclusive, this phenomenon then leads to the process of association, integration, complementation, and sublimation.